2018
DOI: 10.1016/j.jsxm.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex Hormones and Age on Brain Volume in Post-Menopausal Women

Abstract: Background Investigation of the effect of sex hormones on the brain volume in women provides a unique opportunity to examine menopause-related morphometric alterations. Aim To evaluate brain morphological alterations in post-menopausal women using voxel-based morphometry and its correlations with sex hormone levels. Methods 20 Pre-menopausal women and 20 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 25 publications
4
51
1
Order By: Relevance
“…For instance, compared with premenopausal women, postmenopausal women have lower gray matter volumes in the supplementary motor area and other frontal (e.g., inferior frontal gyrus) and temporal (e.g., superior temporal gyrus) regions, and across women, volumes were positively correlated with estradiol . Although pre‐ and post‐menopausal women also differed in hippocampal volume, findings did not withstand corrections for age . In other work, though, hippocampal volume was positively linked to verbal memory in postmenopausal women, providing early indication that gray matter reductions not only reflect estradiol decline, but also have implications for cognition.…”
Section: Menopausementioning
confidence: 87%
See 1 more Smart Citation
“…For instance, compared with premenopausal women, postmenopausal women have lower gray matter volumes in the supplementary motor area and other frontal (e.g., inferior frontal gyrus) and temporal (e.g., superior temporal gyrus) regions, and across women, volumes were positively correlated with estradiol . Although pre‐ and post‐menopausal women also differed in hippocampal volume, findings did not withstand corrections for age . In other work, though, hippocampal volume was positively linked to verbal memory in postmenopausal women, providing early indication that gray matter reductions not only reflect estradiol decline, but also have implications for cognition.…”
Section: Menopausementioning
confidence: 87%
“…There is emerging evidence for structural decrements associated with menopause and some suggestion that they are related to declining estradiol levels. For instance, compared with premenopausal women, postmenopausal women have lower gray matter volumes in the supplementary motor area and other frontal (e.g., inferior frontal gyrus) and temporal (e.g., superior temporal gyrus) regions, and across women, volumes were positively correlated with estradiol . Although pre‐ and post‐menopausal women also differed in hippocampal volume, findings did not withstand corrections for age .…”
Section: Menopausementioning
confidence: 88%
“…In contrast, older women showed increased left posterior-superior hippocampal GMV compared to older men. It might well be the case that for women hormonal changes after menopause modulate these specific hippocampal GMV differences in comparison to men 11 . Additional information on this effect is provided in the Supplement.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the greatest effect was seen in patients who experienced cognitive deficits prior to initiating hormone therapy. A further study demonstrated decreases in gray matter volume in the superior temporal gyrus, inferior frontal gyrus, olfactory cortex and supplementary motor area in postmenopausal women when correcting for age [47]. This provides conflicting evidence for the effects of E2 treatment on brain volume.…”
Section: Cognitive and Morphological Changes With Changing E2 Levelsmentioning
confidence: 96%